Identification and characterisation of two high-affinity glucose transporters from the spoilage yeast Brettanomyces bruxellensis. Issue 17 (30th October 2019) - Tiukova, Ievgeniia A; Møller-Hansen, Iben; Belew, Zeinu M; Darbani, Behrooz; Boles, Eckhard; Nour-Eldin, Hussam H; Linder, Tomas; Nielsen, Jens; Borodina, Irina
ABSTRACT: The yeast Brettanomyces bruxellensis (syn. Dekkera bruxellensis ) is an emerging and undesirable contaminant in industrial low-sugar ethanol fermentations that employ the yeast Saccharomyces cerevisiae . High-affinity glucose import in B. bruxellensis has been proposed to be the mechanism by which this yeast can outcompete S. cerevisiae . The present study describes the characterization of two B. bruxellensis genes ( BHT1 and BHT3 ) believed to encode putative high-affinity glucose transporters. In vitro -generated transcripts of both genes as well as the S. cerevisiae HXT7 high-affinity glucose transporter were injected into Xenopus laevis oocytes and subsequent glucose uptake rates were assayed using 14 C-labelled glucose. At 0.1 mM glucose, Bht1p was shown to transport glucose five times faster than Hxt7p. pH affected the rate of glucose transport by Bht1p and Bht3p, indicating an active glucose transport mechanism that involves proton symport. These results suggest a possible role for BHT1 and BHT3 in the competitive ability of B. bruxellensis . Abstract : Identification and characterization of two high-affinity glucose transporters from the spoilage yeast Brettanomyces bruxellensis .